Twilight of the tigers peace efforts and power struggles in Sri Lanka - Peiris, G. H. (New Delhi ; Oxford : Oxford University Press, 2009)
This book focuses on the political vicissitudes of Sri Lanka since the initiation in December 2001 of a ceasefire that sought to end the violent confrontation between the LTTE and the Sri Lankan security forces. It shows that the ceasefire did not mark a cessation of hostilities.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sri Lanka -- History -- Civil War, 1983-; Sri Lanka -- History -- Civil War, 1983- -- Armistices; Sri Lanka -- Politics and government -- 1978-